Exploration of Students' Difficulties and Teachers' Solutions in Narrative Writing Learning in Elementary Schools - Sri wulan Anggraeni; Dadang Sunendar; Isah Cahyani (Universitas Pendidikan Ganesha, 2024)
This study reveals that many students struggle with narrative writing, particularly in terms of word choice, theme, and grammar, while the solutions provided by teachers often do not meet individual needs. The aim of this study is to identify students' preferences, challenges, and solutions in narrative writing. A descriptive-qualitative approach was employed, involving 166 fifth-grade students from an elementary school as subjects. Data were collected through observation, semi-structured interviews with teachers, and questionnaires c filled out by students and then analyzed thematically, focusing on difficulties in idea development, vocabulary usage, writing structure, and the solutions offered by teachers. The results show that although students have a high interest in writing stories, they face difficulties in creating a coherent storyline and in developing characters and settings. Other major challenges include vocabulary use and grammar comprehension. Students' preference for group writing and gamification elements indicates great potential for increasing their motivation and engagement. Strategies such as group brainstorming and the use of visual aids have proven effective in helping students design better storylines, enhance creativity, and overcome limitations in narrative structure. In conclusion, collaborative approaches, gamification, and interactive technology can effectively improve students' narrative writing skills by addressing their individual preferences and challenges.